Experimental reproduction of necrotic enteritis in chickens: a review. Issue 3 (3rd May 2016) - Prescott, John F.; Smyth, Joan A.; Shojadoost, Bahram; Vince, Andrew
ABSTRACT: This review discusses key factors important in successful experimental reproduction of necrotic enteritis (NE) in chickens, and how these factors can be adjusted to affect the severity of the lesions induced. The critical bacterial factor is the need to use virulent, netB -positive, strains of Clostridium perfringens ; disease severity can be enhanced by using netB -positive C. perfringens strains that are also tpeL -positive, by the use of young rather than old broth cultures, and by the number of days of inoculation and the number of bacteria used. Use of cereals rich in non-starch polysaccharides can enhance disease, as does use of animal proteins. Administration of coccidia, including coccidial vaccines, combined with netB -positive C. perfringens, increases the severity of experimentally-induced NE. Dietary manipulation may be less important in coccidia-based models since the latter are so effective. Disease scoring systems and welfare considerations are discussed.